ChemInform Abstract: 4‐Dodecylbenzenesulfonic Acid (DBSA) Promoted Solvent‐Free Diversity‐Oriented Synthesis of Primary Carbamates, S‐Thiocarbamates and Ureas. Issue 6 (21st January 2016) - Sardarian, Ali Reza; Inaloo, Iman Dindarloo
Abstract: A highly efficient and environmentally benign method for the synthesis of primary carbamates, S‐thiocarbamates, and ureas is introduced.